Mapeamento de habitats marinhos da Plataforma continental interna da Praia de Iracema – Fortaleza -Ceará - Pinheiro, Lidriana de Souza (2019)
The present work has the objective of characterizing marine habitats of the continental shelf of Iracema beach in Fortaleza, Ceara, from the integrated analysis of the benthic substract. This characterization was based on the background bathymetry, sedimentology and benthic fauna and flora of the landscape fragments of data collected on the site and analyzed in the laboratory. The particle size analyzes on the 20 field samples indicated a fraction distribution of gravel, medium, fine and very fine sand and biogenic fractions. The sands class are in isolated spots, with a percentage of 90 to 100%, with some containing mica The medium sand occurs in the NW portion of the area. The biogenic deposits correspond to sediments consisting of fragments of marine animals and calcareous algae. The biodiversity highlight of the biodiversity was found in Station3, where were found examples of the Echinodermata, Mollusca, Porifera, and Annelida phyla. In the samples substantially sandy, it was observed the presence of organisms belonging to the phylum Mollusca - Class Bivalvia. The biotic and abiotic data interaction (sedimentological and bathymetric) allowed the mapping of four marine habitats, classified in Levels1and 2, codes A (Marine Habitats) and A1 (Littoral Rock and other hard substrata), of the classification proposed by EUNIS, 2012